2017
DOI: 10.3390/e19100517
|View full text |Cite
|
Sign up to set email alerts
|

Participation Ratio for Constraint-Driven Condensation with Superextensive Mass

Abstract: Broadly distributed random variables with a power-law distribution f (m) ∼ m −(1+α) are known to generate condensation effects. This means that, when the exponent α lies in a certain interval, the largest variable in a sum of N (independent and identically distributed) terms is for large N of the same order as the sum itself. In particular, when the distribution has infinite mean (0 < α < 1) one finds unconstrained condensation, whereas for α > 1 constrained condensation takes places fixing the total mass to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…On the other hand, several authors, on the basis of general thermodynamic arguments, have argued that this negative-temperature phase should not be a genuine thermodynamic equilibrium one (e.g., see [19][20][21][22][23][24][25]). In this paper we provide an answer to all of these open questions, by computing explicitly the microcanonical partition function of the DNLSE close to the β = 0 line for large N , using large-deviation techniques similar to those employed in [26][27][28][29]. In particular, the study of the microcanonical entropy here presented closely follows the large deviations study of runand-tumble particles in [28], though the context of the latter was entirely different.…”
Section: Model and State Of The Artmentioning
confidence: 98%
“…On the other hand, several authors, on the basis of general thermodynamic arguments, have argued that this negative-temperature phase should not be a genuine thermodynamic equilibrium one (e.g., see [19][20][21][22][23][24][25]). In this paper we provide an answer to all of these open questions, by computing explicitly the microcanonical partition function of the DNLSE close to the β = 0 line for large N , using large-deviation techniques similar to those employed in [26][27][28][29]. In particular, the study of the microcanonical entropy here presented closely follows the large deviations study of runand-tumble particles in [28], though the context of the latter was entirely different.…”
Section: Model and State Of The Artmentioning
confidence: 98%
“…It has been found that, in many cases, exhibits a singular behavior, in that it is non-differentiable around some value (or values) of the fluctuating variable [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Such singularities have an origin akin to those observed in the thermodynamic potentials of systems at criticality.…”
Section: Introductionmentioning
confidence: 99%
“…Similar ideas hold for the analysis of random partition functions and were used in the study of the Sinai model [24,25]. In the context of a run-and-tumble model and the combination phenomenon, these insights are well understood [26,27]. Roughly speaking, one can see that the largest summand is of the order of the total sum, a theme which is already known.…”
Section: Introductionmentioning
confidence: 80%